PENGARUH PERUBAHAN IKLIM TERHADAP OPTIMASI KETERSEDIAAN AIR DI IRIGASI WAY MITAL PROPINSI MALUKU - Hukom, Edison; Limantara, Lily Montarcih; Andawayanti, Ussy (Jurnal Teknik Pengairan: Journal of Water Resources Engineering, 2012)
Global climate change affects to temperature, relative humidity, solarradiation length, wind speed, rainfall and river discharge. Due to climate change the high of rainfall intensity impact on river discharge fluctuations in the wet anddry season. Floods and droughts as anatural event are more often occurred at this time. Waymital Irrigation area has a127 hectares command area consisting of the fourtertiary those are 7 hectares Kairatutertiary, 10 hectares Gembatertiary, 10 hectares Hatusuatertiary and 100 hectares way Mitaltertiary, therefore to deal with that extreme impact, required a systematically irrigation management plansin order to be still profitable, especially for farmers.The methodology used in the analysis of irrigation water availability optimization at Mital Way command area using the Simplex Linear Programming that will be obtained cropping area, discharge and maximum benefit of agricultural production.Based on the analysis results indicates that has occurred the climate change on Way mital command area in 2009 that is marked by a shifted in the rainy and dry seasons and increased the amount of annual rainfall. Increasing the amount of rainfall has an impact on the volume availability of water intake changes, before the climate change, the volume availability of water intheintake (cropping season) are MTI =699000 m3, MTII = 444 000 m3and MTIII =502 000 m3. While from the study result also showed that after the occurrence of climate change, volume of water available in the intake are MTI =715000 m3, MTII = 487000 m3and MTIII =537000 m3. Volume of water availability from the optimization of the existing cropping pattern at Way Mitalboth before and after climate change is still sufficient to water requirement for everycropping season and the difference inprofit is 418.875.000 rupiahs peryear which is obtained from agricultural production.Keywords: Climate Change, WaterAvailability, Linear Programming.